1996
DOI: 10.1111/j.1399-3054.1996.tb00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold hardiness and water relations parameters in Rhododendron cv. Catawbiense Boursault subjected to drought episodes

Abstract: We determined whether increase in cold hardiness of Rhododendron cv. Catawbiense Boursault induced by water stress was correlated with changes in tissue water relations. Water content of the growing medium was either maintained near field capacity for the duration of the study or plants were subjected to drought episodes at different times between 15 July and 19 February. Watering during a drought episode was delayed until soil water content decreased below 0.4 m3 m−3 then watering was resumed at a level to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
12
2
Order By: Relevance
“…For instance, water-stressed plants accumulate a higher concentration of solutes (i.e. sugars, proteins) in their tissues that depress FP (Chen et al 1977;Goldstein et al 1985;Anisko and Lindstrom 1996). However, we found that FP increased in the leaves of plants growing inside OTCs, suggesting that plants growing under warmer conditions modify the processes of ice formation in their tissues rather than adjust the osmotic potential of their tissues in response to an increase in the soil water deficit.…”
Section: Discussioncontrasting
confidence: 59%
“…For instance, water-stressed plants accumulate a higher concentration of solutes (i.e. sugars, proteins) in their tissues that depress FP (Chen et al 1977;Goldstein et al 1985;Anisko and Lindstrom 1996). However, we found that FP increased in the leaves of plants growing inside OTCs, suggesting that plants growing under warmer conditions modify the processes of ice formation in their tissues rather than adjust the osmotic potential of their tissues in response to an increase in the soil water deficit.…”
Section: Discussioncontrasting
confidence: 59%
“…Several studies have reported that water‐soluble carbohydrates depress FP, and their accumulation is positively related to drought survival (Streeter et al ., 2001; Merchant et al ., 2006; Monson et al ., 2006). Moreover, other studies reported that the lower FP of water‐stressed plants result from a higher of solute concentration in their tissues (Chen et al ., 1977; Goldstein et al ., 1985; Anisko & Lindstrom, 1996). Hence, decreases in the FP at the end of the growing season are likely to be related to plant responses to drought rather than to ambient temperatures alone.…”
Section: Discussionmentioning
confidence: 99%
“…Frost injury in freezing-sensitive species is induced mainly through extracellular ice formation, which dehydrates mesophyll tissues by extracting symplastic water, but may directly disrupt the bundle sheath cells of C 4 plants (Ashworth and Pearce, 2002). However, by altering their biochemical composition under chilling temperatures, cold-acclimated plants can accumulate compatible osmolytes in cells, which cause a decline in water potential and increase resistance to dehydration (Goldstein et al , 1985; Aniśko and Lindstrom, 1996), also improving their resistance to freezing (Smallwood and Bowles, 2002). The data reported here are consistent with this mechanism, showing that values of Ψ leaf and Ψ osmotic decreased in plants exposed to the chilling pre-treatment, indicating significant osmoregulation, especially for those in the cold-acclimating group (Fig.…”
Section: Discussionmentioning
confidence: 99%